PERBEDAAN TINGKAT KECEMASAN SUAMI YANG DIBERI DAN TIDAK DIBERI PENDIDIKAN KESEHATAN TENTANG PERSALINAN SECTIO CAESAREA DI RSU DELIMA MEDAN TAHUN 2021 - HELENA FRANSYSCA (LP2MTBM MAKARIOZ, 2021)
Anxiety is a subjective feeling that is an unusual feeling of discomfort, tension and is an emotional reaction to the perceptionof danger. The purpose of this study was to find out the Difference in Anxiety Levels of Husbands Given and Not GivenHealth Education About Sectio Caesarea Childbirth in Wives at Pomegranate Medan Hospital in 2021. This research usesthe design or design of experimental quasi research. The population in this study were all husbands who accompanied wiveswho underwent the process of childbirth sectio cesarea at RSU Pomegranate Medan from December 2020 - January 2021.Sampling is done using simple random sampling as many as 70 people. The data analysis was conducted with univariateanalysis and bivariate analysis to see differences in the level of anxiety of the husband who was affected by theadministration or non-provision of penkes to the delivery of Sectio Cesarea for the husband. Hypothesis testing usesstatistical tests with independent sample tests. The results of the study using the T Independent simple T-test showed therewas a difference in anxiety of the group who were given penkes and not given penkes with pvalue = 0.000 (p<α = 0.05). It isexpected to the nurse to provide counseling, health education, related to the delivery of Sectio Caesarea in reducing theanxiety of the husband.